On the composition dependence of the microscopic structure, thermodynamic, dynamic and dielectric properties of water-dimethyl formamide model mixtures. Molecular dynamics simulation results - H. Dominguez; O. Pizio (Condensed Matter Physics, 2017)
Isothermal-isobaric molecular dynamics simulations have been performed to examine an ample set of properties of the model water-N,N-dimethylformamide (DMF) mixture as a function of composition. The SPC-E and TIP4P-Ew water models together with two united atom models for DMF [Chalaris M., Samios J., J. Chem. Phys., 2000, 112, 8581; Cordeiro J., Int. J. Quantum Chem., 1997, 65, 709] were used. Our principal analyses concern the behaviour of structural properties in terms of radial distribution functions, and the number of hydrogen bonds between molecules of different species as well as thermodynamic properties. Namely, we explore the density, excess mixing molar volume and enthalpy, the heat capacity and excess mixing heat capacity. Finally, the self-diffusion coefficients of species and the dielectric constant of the system are discussed. In addition, surface tension of water-DMF mixtures has been calculated and analyzed.